Social farming and work inclusion initiatives for adults with autism spectrum disorders: A pilot study. (1st April 2019) - Torquati, Biancamaria; Stefani, Gianluca; Massini, Giulio; Cecchini, Lucio; Chiorri, Massimo; Paffarini, Chiara
Highlights: We assess the attitude of adults with autistic spectrum disorders to carry out agricultural and animal husbandry work that can promote work inclusion. We set-up an experimental evaluation tool, based on an already validated medical assessment tool, to measure performance in farming activities' as an alternative construction. We verify the possibility of work inclusion for adults with autistic spectrum disorder on farms. Abstract: In recent years, an increasing number of social farming initiatives have involved adults with autism spectrum disorders, both to improve their life conditions and promote their work inclusion. Several studies have assessed these experiences, showing that the participants derive important benefits from being part of a social community, working in the countryside, and establishing a good relationship with the farmer. This paper aims to assess the ability of 9 adults with autism spectrum disorders – who attend an adult day care centre in the Umbria region of Italy – to carry out agricultural and animal husbandry activities. Results from panel data analysis show that the activity of olive grove, indoor cleaning, and tidying at the agritourism farms has a considerable positive effect on the performances of the adults with autism spectrum disorders. Moreover, the adults studied prefer the activities in a greenhouse over those occurring inside (e.g., agritourism farm or the warehouse) and outside (e.g., vegetable, olive, and grape production). Further, the higher the precision level required to perform an action, the lower is their observed performance. Generally, the tasks that receive the highest evaluations are those in which the autistic person can relate with other people and/or animals. These findings confirm the role of social farming in developing working and relational skills in adults with autism spectrum disorders.